God's Bridle: John Calvin's Application of Natural Law - Pryor, C. Scott (Journal of law and religion, 2006)
Natural law has made a comeback in legal philosophy. The revival of natural law thinking in the legal academy began about thirty years ago and has managed to gain a seat at the table in current jurisprudential discussions. Defining natural law, Brian Bix declares that it "claims that there are fundamental and evaluative connections between the universe, human nature, and morality." These connections need not have a Christian or even a theistic foundation. A belief in moral realism, that is, the propositions that "(1) there is an objective reality, (2) human beings can know something about it, and (3) there are some things that everyone can, and some things that everyone ought to, do in response to what they know," ties together theistic and non-theistic versions of natural law. Yet many prominent contemporary natural law theorists—J. Budziszewski, John Finnis, Robert George, and Russell Hittinger —are Roman Catholic. Despite the fact that Finnis and George develop their natural law arguments without reference to any metaphysical states of affairs or transcendent truth claims, natural law continues to be associated with Thomas Aquinas and the subsequent scholastic tradition. Thus, even standards that Finnis and George derive from the internal rationality of law strike some as disguised theology.